Chemoenzymatic synthesis of structured triacylglycerols containing eicosapentaenoic and docosahexaenoic acids - Haraldsson, Gudmundur G.; Halldorsson, Arnar; Kuls, Elin (Journal of the American Oil Chemists' Society, 2000)
Abstract There are indications in the recent literature that the location of polyunsaturated fatty acids, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), in triacylglycerols (TAG) may influence their oxidative stability. To address that question, two types of structured lipids were designed and synthesized: firstly, a TAG molecule possessing pure EPA or DHA at the mid‐position with stearic acid at the outer positions; and secondly, a TAG molecule possessing pure EPA or DHA located at one of the outer positions with stearic acid at the mid‐position and the remaining end position. The former adduct was synthesized in two steps by a chemoenzymatic approach. In the first step 1,3‐distearolyglycerol was afforded in good yield (74%) by esterifying glycerol with two equivalents of stearic acid in ether in the presence of silica gel using Lipozyme TM as a biocatalyst. This was followed by a subsequent chemical esterification with pure EPA or DHA using 1‐(3‐dimethylaminopropyl)‐3‐ethylcarbodiimide as a coupling agent in the presence of 4‐dimethylaminopyridine in dichloromethane in excellent yields (94 and 91, respectively). The latter adduct was synthesized in two enzymatic steps. In the first step tristearoylglycerol was prepared in very high yield (88%) by esterifying glycerol with a stoichiometric amount of stearic acid under vacuum at 70–75°C using an immobilized Candida antarctica lipase without a solvent. That adduct was subsequently treated in an acidolysis reaction with two equivalents of EPA or DHA without solvent at 70–75°C or in toluene at 40°C in the presence of Lipozyme to afford the desired product in moderate yields (44 and 29%, respectively).